The Use of Phrasal Verbs on Twitter Accounts - Cindy Aulia Deviani; Rika Mutiara (Journal on Education, 2023)
This research explored the most frequent types of phrasal verbs, the 10-most-frequent phrasal verbs used, and the 5-most-frequent simple verbs used to build phrasal verbs on Twitter accounts. This study used qualitative research to collect qualitative data and used analytical techniques. The data were taken from the tweets of Barack Obama and Katy Perry. After collected the types of phrasal, phrasal, and simple verbs, the data were analyzed by categorizing them. After that, the frequency were calculated and converted to a percentage. The researcher examined as many as 379 tweets from both accounts. The frequency of types of phrasal verbs are idiomatic meaning (73%) and literal meaning (27%). The 10-most-frequent phrasal verbs are tune in, look at, get to, look forward to, sign up, reflect on, catch up, come up, check out, and live in. The 5-most-frequent simple verbs are look, tune, get, come, and live. The implications of this research can be used to prepare teaching materials about phrasal verbs. High-frequency phrasal verbs such as tune in, look at, get to can be included in teaching materials. After that, the teacher can explain types of phrasal verbs, namely literal and idiomatic meanings, and gives examples, so students understand this material.